Risk Factors Related to Anemia in Oil Palm Plantation Workers in Ogan Komering Ilir Regency - Wulandari, Wiwiet; Vivi Oktari; Sri Wahyuningsih (Universitas PGRI Palembang, 2025)
Anemia is a common health problem worldwide, especially in developing countries. Oil palm plantation workers are at high risk of developing anemia due to various factors such as diet, working conditions, and pesticide exposure. This study analyzes the risk factors associated with anemia in oil palm plantation workers in Ogan Komering Ilir Regency. The research method used was an analytical survey with a cross-sectional approach. Data were collected through structured interviews and questionnaires with 33 oil palm plantation workers. The variables studied included age, occupation, level of knowledge, family support, and specific exposure. Statistical analysis was performed using the chi-square test. The results showed that the incidence of anemia in plantation workers reached 14.7%. Occupational factors (p = 0.011) and family support (p = 0.005) had a significant relationship with the incidence of anemia. However, no significant relationship was found between age (p = 0.414), level of knowledge (p = 1.000), and exposure (p = 0.634) with the incidence of anemia. This study concludes that occupational factors and family support contribute to the incidence of anemia in oil palm plantation workers. Further research is needed to explore other risk factors that may influence the incidence of anemia in this group.